1985
DOI: 10.1080/01431168508948511
|View full text |Cite
|
Sign up to set email alerts
|

Standardized principal components

Abstract: In remote sensing, principal components analysis is usually performed using unstandardized variables. However, the use of standardized variables yields significantly different results. In this paper principal components of two LANDSAT MSS subscenes were separately calculated using both methods. The result indicate substantial improvement in signal-to-noise ratio and image enhancement by using standardized variables in the principal components analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
115
0
4

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(119 citation statements)
references
References 8 publications
0
115
0
4
Order By: Relevance
“…In the future, selection of the suitable image bands for change detection using MPCA and determination of the threshold of each bands are both important to produce highly accurate change detection results. Although the MPCA is the simplest and easiest to implement method, it proved to be too scene-dependent, which has also been reported by several authors (Singh and Harrison 1985). In addition, MPCA produce a more direct interpretation linked with the vegetation damage and recovery processes after forest fires in the study area.…”
Section: Principal Component Analysismentioning
confidence: 93%
See 1 more Smart Citation
“…In the future, selection of the suitable image bands for change detection using MPCA and determination of the threshold of each bands are both important to produce highly accurate change detection results. Although the MPCA is the simplest and easiest to implement method, it proved to be too scene-dependent, which has also been reported by several authors (Singh and Harrison 1985). In addition, MPCA produce a more direct interpretation linked with the vegetation damage and recovery processes after forest fires in the study area.…”
Section: Principal Component Analysismentioning
confidence: 93%
“…The remaining component (PC6, PC7, and PC8) were quite sensitive to noise along with variation of vegetation coverage or do not display any features of significance to the study. Furthermore, some researchers found that the eigenvector characteristics of three additional principal components (PC6, PC7, and PC8) gave little more information than the first five PCs because they have eigenvalue variabilities less than 1% and did not show a useful specific form in further land cover change detection (Singh andHarrison 1985, Garcia-Haro et al 2001).…”
Section: Principal Component Analysismentioning
confidence: 99%
“…Most of the images obtained were captured late in the dry season, or soon after the majority of fires generally occur, to maximize mapping accuracy. The spectral signatures of burned areas could be better distinguished after principal components analysis (PCA) (Richards, 1984;Singh and Harrison, 1985;Fung and LeDrew, 1987) than in the raw data. Burned areas were subsequently separated from unburned areas with a supervised classification (parallelepiped) of the principal components (PCs).…”
Section: Fire Scar Mappingmentioning
confidence: 99%
“…Principal component analysis (PCA) is a multivariate statistical technique that selects uncorrelated linear combinations (eigenvector loadings) of variables in such a way that each successively extracted linear combination or principal component (PC) has a smaller variance 21 . The eigenvector matrix used to perform PCA for each subset was examined to identify which PC contained the target (mineral) information.…”
Section: Principal Component Analysis Methodsmentioning
confidence: 99%